2018
DOI: 10.1001/jamanetworkopen.2018.5547
|View full text |Cite
|
Sign up to set email alerts
|

Association of Ankle-Brachial Indices With Limb Revascularization or Amputation in Patients With Peripheral Artery Disease

Abstract: Key Points Question Are ankle-brachial indices associated with limb outcomes in community-dwelling patients with peripheral artery disease as identified by computational approaches applied to electronic health records? Findings In this cohort study of 1413 community-dwelling patients, peripheral artery disease was identified and limb outcomes were retrieved by computational approaches applied to electronic health records. Ankle-brachial indices of 1.4 or gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 46 publications
0
15
1
1
Order By: Relevance
“…The influence analysis showed that only one study had a significantly heavier weight than others; 37 however, the overall association between MAC and risk of LLA did not significantly change when removing it by the final computation, as well as removing each of the other studies, thus suggesting a good consistency for our final results. Moreover, our sensitivity analysis showed that the pooled estimate was not significantly affected by lower quality studies.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The influence analysis showed that only one study had a significantly heavier weight than others; 37 however, the overall association between MAC and risk of LLA did not significantly change when removing it by the final computation, as well as removing each of the other studies, thus suggesting a good consistency for our final results. Moreover, our sensitivity analysis showed that the pooled estimate was not significantly affected by lower quality studies.…”
Section: Discussionmentioning
confidence: 84%
“…Among these, 37 articles were excluded (27% of fully reviewed papers were excluded because they did not study amputations as an outcome; Figure 1). Finally, 15 articles were selected for inclusion in the meta-analysis; 2438 their main characteristics are reported in online supplemental Table II.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous authors have shown the histopathological findings of extensive MAC in amputated limbs 19–22 and the association of MAC with ulcer, gangrene, and amputation. 2326,3032…”
Section: Discussionmentioning
confidence: 99%
“…27 Moreover, an elevated ankle-brachial index (ABI), considered an expression of noncompressible ankle arteries as a consequence of MAC, is associated with a high prevalence of occlusive tibial and pedal arch disease 28 and occlusive PAD 29 and is as equally prognostic in predicting the need for amputation as a low ABI. 3032…”
Section: Introductionmentioning
confidence: 99%